Women Traders Livelihoods in Tourism Area of Lok Baintan Floating Market - Arisanty, Deasy; Putro, Herry Porda Nugroho; Normelani, Ellyn; Anis, Moh. Zaenal Arifin (Journal of Indonesian Tourism and Development Studies, 2020)
The destination of tourism in South Kalimantan Province was Lok Baintan Floating Market. Lok Baintan Floating Market was an icon of Banjar cultural tourism. The objective of this research was to analyze the livelihoods of women traders in Lok Baintan Floating Market as a tourism area. It also to analyze the influential factor of women trader livelihood in the Lok Baintan Floating Market. Data collection used survey methods and questionnaires. The number of Women traders was 50 people. The analysis used was by calcifying index values and factor tests. Livelihood index values determined the level of livelihood of women traders. Factor tests determined the factors that most influence for livelihood level of women traders. The results showed that the livelihoods of Women traders were in the moderate category. It means that natural resource assets, financial assets, human resource assets, physical assets, social assets, access, and activities were still able to support women's lives in tourist areas. Physical assets had the highest value of the sustainable livelihood approach (SLA), which was 73.33%. Financial assets had the lowest value of SLA, which was 50.00%. The influences of factor 1 and factor 2 were 62.778% for women trader livelihoods. Factors in group 1 were natural resource assets, financial assets, and human assets. The second factors were physic assets, activity and social assets.Keywords: livelihood, sustainable, tourism, women trader.